Peningkatan Kompetensi Penyuluh Keluarga Berencana Provinsi Jawa Timur Melalui Diklat Berbasis E-Learning - Widi Asih Nurhajati (International Consortium of Education and Culture Research Studies, 2018)
A Civil Servant is required to have high competence in accordance with the duties and functions. However, the result of competency test conducted by BKKBN showed that from 2,255 Family Planning Extension Worker/Penyuluh Keluarga Berencana (PKB) in East Java, only 822 people (36.5%) achieved above standard, 32 people (1.4%) as per standard, and 1,401 people (62.1%) still need follow-up development because they hadn’t up to the standard required. One of the efforts to increase PKB’s competence is by training using more effective, efficient, and reachable method. Due to the training’s limited facilities and human resources in BKKBN Representative of East Java Province, the research was conducted to analyze the e-learning-based training method in order to improve the competence of PKB. This research is a descriptive research using secondary data through literature study from various sources. E-learning conducted by BKKBN in 2012 has various weaknesses, both in context, input, and process. Development of e-learning in the future must accommodate the learning needs of PKB, both in terms of competence, facilities infrastructure, human resources managers, and rewards so that PKB can learn the material independently without having to follow the conventional training class. When learning independence has increased, learning outcomes will increase, therefore the competence of PKB can meet the standards.